Modality-specific attentional startle modulation during continuous performance tasks: A brief time is sufficient - Alhadad, S.; Lipp, Ottmar; Purkis, H. (Wiley-Blackwell Publishing, Inc., 2008)
Attentional startle modulation has been found to be modality specific in continuous performance tasks (CPTs) and modality nonspecific in trial-structured tasks. Experiment 1 investigated whether attentional blink modulation in a CPT would change if a trial structure was imposed. Participants performed a visual CPT either continuously (CONT), or during brief periods of time signaled by a change in screen color with stimuli either presented all the time (MIXED) or only during the trial segments (DISC). Contrary to expectation, evidence for modality-specific attentional startle modulation - smaller acoustic startle during targets than during nontargets - was strongest in Groups MIXED and DISC. Experiment 2 confirmed that this pattern of results was present during the first stimulus of the task period in group DISC. This suggests that the continuous nature of a task is not critical in determining the attentional mechanisms engaged. Copyright © 2008 Society for Psychophysiological Research.